Transformasi Politik dan Prospek Bagi Perdamaian Positif Berkelanjutan di Aceh - Suadi Zainal; Kamarulzaman Askandar (Puslatbang KHAN, 2013)
A peace agreement does not automatically create a situation of positive peace in a post conflict area. In fact, many peacefully resolved conflicts have reverted back to become violent after a few years. The people living in these areas are always hopeful that a positive peace is achieved after a peace agreement, even if it is something very difficult to achieve. A peace agreement like the Helsinki MOU is only able to achieve a situation of negative peace in Aceh. To achieve a situation of positive peace, concrete actions must be undertaken by all stakeholders, especially the rulers of Aceh, or the Acehnese government. At the very least, there are three important aspects that must be observed by peace actors: politics, economic, and social. This paper will however only focus on two of these – politics and economy. The paper will analyse the political transformation and efforts made by the Aceh government to change the political situation and economy as a way to fulfill the needs of the Acehnese people. Based on this, a prediction can be made of the prospect to achieve sustainable positive peace in Aceh. Lastly, it is hoped that this study can contribute some thoughts to peace and development actors in their efforts to build peace in post-conflict areas.